Polyphenols and radiotherapy: literature review of preclinical and clinical evidence - Wiśniowski, Maksymilian; Kulig, Klaudia; Wiśniowska, Ada; Buczek, Kacper; Zwierzchlewska, Patrycja; Kulszo, Katarzyna; Baszun, Bartłomiej; Bijak, Piotr; Kozłowska, Aleksandra; Dąbrowska, Julia (Journal of Education, Health and Sport, 2025)
Introduction and aim: Radiotherapy is a fundamental component of cancer treatment but is limited by tumor radioresistance and damage to healthy tissues. Polyphenols—plant-derived compounds with antioxidant, anti-inflammatory, and anticancer properties—have gained attention for their potential to modulate radiotherapy outcomes. This review aims to evaluate preclinical and clinical evidence on the effects of selected polyphenols in combination with radiotherapy. Materials and methods: A comprehensive literature search was conducted using PubMed, ScienceDirect, ResearchGate, and Google Scholar, focusing on studies from the last two decades. Search terms included: radiotherapy, radiation. polyphenols, curcumin, genistein, chrysin, ellagic acid, resveratrol, quercetin, apigenin, epicatechin, kaempferol, caffeic acid, gallic acid. Both in vitro and in vivo studies were included, as well as available clinical trials. Results: Several polyphenols—including curcumin, genistein, ellagic acid, resveratrol, and quercetin—demonstrated the ability to enhance radiosensitivity in tumor cells or protect normal tissues. Curcumin and genistein have shown early clinical benefits, particularly in head and neck and prostate cancer patients. However, most polyphenols remain in the preclinical stage. Conclusion: Polyphenols show promise as adjuncts to radiotherapy, with context-dependent radiosensitizing or radioprotective effects. Further clinical trials are necessary to validate efficacy, safety, and optimal dosing before integration into standard oncology protocols.